Voter Turnout in Direct Democracy: Theory and Evidence - Morten Søberg; Thomas P. Tangerås (The Research Institute of Industrial Economics (IUI), 2003)
We analyse voter turnout as a function of referendum types. An advisory referendum produces advice that a legislature may or may not take into account when choosing between two alternatives, whereas a binding referendum generates a decisive decision. In theory, voter turnout should be higher under binding than advisory referendums, higher in small than large electorates and higher in close than less close referendums. These predictions are corroborated by evidence from 230 local referendums in Norway. For example, a shift from an advisory to a semi-binding referendum leads to an average increase in voter turnout by 11.5 percentage points.
Keywords: D72; 330; Voting Behaviour; Referendum Types; Rational Choice; Wahlverhalten; Rationales Verhalten